Advances in paediatric urology. Issue 10099 (9th September 2017) - Diamond, David A; Chan, Ivy H Y; Holland, Andrew J A; Kurtz, Michael P; Nelson, Caleb; Estrada, Carlos R; Bauer, Stuart; Tam, Paul K H
Summary: Paediatric urological surgery is often required for managing congenital and acquired disorders of the genitourinary system. In this Series paper, we highlight advances in the surgical management of six paediatric urological disorders. The management of vesicoureteral reflux is evolving, with advocacy ranging from a less interventional assessment and antimicrobial prophylaxis to surgery including endoscopic injection of a bulking agent and minimally invasive ureteric reimplantation. Evidence supports early orchidopexy to improve fertility and reduce malignancy in boys with undescended testes. A variety of surgical techniques have been developed for hypospadias, with excellent outcomes for distal but not proximal hypospadias. Pelvi-ureteric junction obstruction is mostly detected prenatally; indications for surgery have been refined with evidence, and minimally invasive pyeloplasty is now standard. The outlook for patients with neurogenic bladder has been transformed by a combination of clean intermittent catheterisation, algorithms of diagnostic investigations, and innovative medical and surgical therapies. Posterior urethral valves are associated with considerable mortality; fetal diagnosis allows stratification of candidates for intervention, but ongoing bladder dysfunction in patients after valve ablation remains a cause of long-term morbidity.